Fiber Bragg gratings - Kashyap, Raman (Optics and photonics.)
Optical fibers have revolutionized telecommunication, becoming the most widely used and the most efficient device for relaying information over long distances. While the market for optical fiber continues to grow, the next stage in the field of communication is the mass delivery of integrated services, such as home banking, shopping, internet services, and entertainment using video on demand. The economies and performance potential will determine the type of technology likely to succeed in the provision of these services. But it is already clear that optical fibers will play a crucial role in.